Development of the First Value Assessment Index System for Off-Label Use of Antineoplastic Agents in China: A Delphi Study - Jiang, Qian; Zeng, Wei; Yu, Jiajie; Liu, Hui; Mao, Mian; Li, Youping (Frontiers in Pharmacology, 2020)
Objective: To develop the first value assessment index system for off-label use of antineoplastic agents in China. Methods: A modified two-round Delphi method was employed to establish consensus within a ﬁeld to reach agreement via a questionnaire or doing interview among a multidisciplinary panel of experts by collecting their feedback to inform the next round, exchanging their individual knowledge, experience and opinions anonymously, and resolving uncertainties. Results: Expert’s positive coefficient was 94.74% in the first round and 100.00% in the second round. In the first round, expert’s authority coefficient for a majority of 61 indicators was ≥ 0.80 (85.2%, ranging from 0.70 to 0.89, mean=0.84) and coefﬁcient of variation for all the 61 indicators was ＜ 22% (ranging from 11.67% to 21.74%, mean=17.4%). In two rounds, the mean expert’s authority coefficient raised to 0.85 (ranging from 0.75 to 0.90), and coefﬁcient of variation for all indicators was  20% (ranging from 10.49% to 19.71%, mean=15.97%). The P-values of Kendall's W test were all < 0.001 for each round. At the end of two rounds, W-value for concordance was 0.395 (=347.494, P<0.0001). The final value assessment index system comprised of 8 domains, 21 subdomains, and 56 indicators. The weight and combination weight of each domain were 0.4211 for therapeutic value, 0.1678 for source and type of evidence, 0.0961 for public feedback/comments, 0.0894 for novelty in drug discovery, 0.0689 for grading of evidence recommendation, 0.0578 for consistency of evidence results, 0.0561 for disease burden, and 0.0428 for ratio of composition/integration. Conclusion: Use of Delphi method to develop the proposed value assessment index system was found scientific and credible. This value assessment index system is highly appropriate for off-label use of antineoplastic agents in China.